Research on the Current Situation and Influencing Factors of College athletics Students' Educational Access Based on Psychological Perspective - Shiyong Chen; Nan Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Competitive athletes face various factors that affect the athletic as well as the academic of the students. Therefore, this statement describes that how athletes cover their mental stress along aggressive struggle of college life. Sports base students have to deal with their academic performance, financial challenges, and progress efficiency of the sports students. The participation of students in sports is important, as it extends the physical activity expands of our society financially, academically, politically, and psychologically. When it comes to the image of an organization or educational institution, the student-athletes is as a highly visible subgroup of students whose performance and visibility is significantly important for the institution. The social environment, including classrooms, can be seen as a system of stress consisting forces that remain relatively stable over time. The data was collected from 242 athletic students. In this paper, the Perceived Level of Learning Anxiety, Perceived Usefulness of Student’s Learning, and Self-Engagement in Learning Course are the Independent Variables. Whereas, Positive Sports Psychology is a Dependent Variable. The research model had three hypothesis statements. The data was collected through online questionnaire portals. Furthermore, the data was analyzed on SMART PLS 3. The results and findings of the data indicated a positive and significant association between the variables.